Ecology of forest insect invasions - Brockerhoff, E. G.; Liebhold, A. M. (Biological invasions, 2017)
Forests in virtually all regions of the world are being affected by invasions of non-native insects. We conducted an in-depth review of the traits of successful invasive forest insects and the ecological processes involved in insect invasions across the universal invasion phases (transport and arrival, establishment, spread and impacts). Most forest insect invasions are accidental consequences of international trade. The dominant invasion ‘pathways’ are live plant imports, shipment of solid wood packaging material, “hitchhiking” on inanimate objects, and intentional introductions of biological control agents. Invading insects exhibit a variety of life histories and include herbivores, detritivores, predators and parasitoids. Herbivores are considered the most damaging and include wood-borers, sap-feeders, foliage-feeders and seed eaters. Most non-native herbivorous forest insects apparently cause little noticeable damage but some species have profoundly altered the composition and ecological functioning of forests. In some cases, non-native herbivorous insects have virtually eliminated their hosts, resulting in major changes in forest composition and ecosystem processes. Invasive predators (e.g., wasps and ants) can have major effects on forest communities. Some parasitoids have caused the decline of native hosts. Key ecological factors during the successive invasion phases are illustrated. Escape from natural enemies explains some of the extreme impacts of forest herbivores but in other cases, severe impacts result from a lack of host defenses due to a lack of evolutionary exposure. Many aspects of forest insect invasions remain poorly understood including indirect impacts via apparent competition and facilitation of other invaders, which are often cryptic and not well studied.